IMPLIKASI HUKUM UMKM PASCA HADIRNYA PUTUSAN MAHKAMAH KONSTITUSI TERKAIT UNDANG-UNDANG CIPTA KERJA - Ikhsan, Muhammad; Ayunda, Rahmi (Maleo Law Journal, 2022)
The passing of Law No. 11 of 2020 on Cipta Kerja in its implementation provides convenience to UMKM actors namely ease in business activities. But, on November 25 2021 Cipta Kerja law was declared unconstitutional conditional so as to raise the question of how to implement the law after the decision of the constitutional court declaring the Cipta Kerja law unconstitutional conditional. In this study, the author wants to examine how to implement before and after the work Cipta Kerja law for UMKM, and also how the status of the legal implications of the Cipta Kerja law on UMKM after the enactment of the Mahkamah Konstitusi (MK) rulling. The research method used is to use non-doctrinal research, which is how to implement a rule or law that is actually embraced by the community in everyday life or also called Law in Action and data collection techniques based on Books, Journals / articles, Websites and Laws. The result of the research conducted that the implementation of the work Cipta Kerja law on UMKM greatly facilitates the business activities of UMKM actors, one of which is from the licensing sector before the enactment of the Cipta Kerja law, but after that the licensing is done based on risk and business scale and licensing services are carried out using the Online Single Submission service. And the implementation after the MK ruling is still enforced by the Cipta Kerja law as it is still constitutional for the next 2 two years after the verdict.